Global Economy Crisis and its Impact on Operational Container Carrier’s Strategy - Jerebić, Vladimir; Pavlin, Stanislav (Promet - Traffic&Transportation, 2018)
The shipping market is an economic derivative of global production and trade, being precariously subject of their cyclic changes, depressions and expansions. This paper analyses the condition of global container shipping market, caused by long-lasting economic and financial crisis that begun in 2008, but is still much visible within the container industry, particularly through overcapacity and low freight rates. It also deals with major changes of maritime container carrier’s management strategies, development and application of advanced transportation, technological, technical, economical, organizational and commercial measures in order to adapt and cope with new business environment. Finally, an attempt is made to forecast the market, potential difficulties and to propose problem-solving measures.